Clinical and histopathological staging in oral squamous cell carcinoma – Comparison of the prognostic significance. (September 2016) - Kreppel, Matthias; Nazarli, Parvin; Grandoch, Andrea; Safi, Ali-Farid; Zirk, Matthias; Nickenig, Hans-Joachim; Scheer, Martin; Rothamel, Daniel; Hellmich, Martin; Zöller, Joachim E.
Graphical abstract: Despite advances and modern radiologic techniques, pTNM has a higher prognostic quality than cTNM. Highlights: There is a clinically relevant discordance between cTNM and pTNM in oral cancer. Discordance was observed in up to 40% of patients with oral cancer. Overestimation of cervical lymph nodes is more common than underestimation. pTNM but not cTNM influence OS significantly in multivariate analysis. Abstract: Background: In oral cancer the prognostic significance of clinical staging (cTNM) is regarded inferior to histopathologic staging (pTNM) after surgery. This is mainly due to the point that the quality of the cTNM strongly depends on the clinical and radiological examination techniques applied and the physician's experience. The aim of this study was to evaluate the prognostic quality of cTNM and pTNM in a single center cohort. Methods: This retrospective study included 392 patients with treatment-naive oral squamous cell carcinoma (OSCC). All patients received primary surgery including a neck dissection. According to tumor stage and histopathologic risk factors patients received adjuvant radiotherapy (RT) or radiochemotherapy (RCT). Prognostic factors were identified in univariate analysis by using the log rank test and in multivariate analysis through Cox regression. Results: Clinical and histopathologic staging showed concordance in 62% for the primary tumor and 59% for cN- and pN-classification. In 58% of the cases of discordance the primary tumor was overstaged. In case of discordance of metastatic spread to the cervical lymph nodes, lymph node involvement showed overstaging in 78%. In univariate analysis cT-, cN-, cT- and pT-classification had a significant impact (p < 0.05) on overall survival (OS). In multivariate analysis only pT- and pN-classification had a significant impact on OS. Conclusion: Despite advances and modern radiologic techniques, pTNM has a higher prognostic quality than cTNM. Discordance between clinical and histopathologic staging was observed in up to 40%. When discordance was observed overstaging for clinical T-stage and clinical N-stage was more likely than understaging.